Characteristics of bovine semen collected, processed, and stored at NABC-Alabang - Bondoc, Orville L. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 1995)
Monthly mean data from the National Artificial Breeding Center (NABC), Alabang, Metro Manila from 1988 to 1992 were analyzed. A total of 197 monthly mean ejaculates was used to evaluate bovine seminal characteristics which included semen volume (ml), pH, normal, abnormal, and total sperm counts (10%/ml), percent motility (initial, before freezing, and after thawing), and number of straws produced per collection.